Utopias and comparative assessments of justice - García Gibson, Francisco (2016)
When we make public policy choices, is it helpful to know how utopia (that is, the perfectly just institutional design) would look? Amartya Sen argues that it is neither necessary, nor sufficient, nor even contributory. He claims that before making a policy choice one should compare several feasible institutional designs to see which promotes justice most (a "comparative assessment" of justice), and that it is misleading to use the perfect design as a standard in those comparisons. Principles of justice are the proper standard. The present article contends that the perfect design has nevertheless an important role to play in the prior task of identifying and refining our principles of justice. It also shows that the perfect design - in at least one sense of this term - may be a legitimate long-term goal for present policy choices.